Assesment of Quality of Life in Patients Undergoing Hemodialysis in RMI, Peshawar - Anam Amin, Mashal Jamil, Awais Ahmad, Aalia Amjad, Zarghuna Khan, Saad Ul Khaliq, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Chronic kidney disease (CKD) is an important cause of morbidity and mortality worldwide. It has been affecting the quality of life (QOL), an important parameter which needs to be addressed. This study assessed QOL keeping in view WHO criteria for patients undergoing hemodialysis at Rehman medical institute (RMI). The study also evaluated the effects of various socioeconomic and demographic factors affecting life of such patients. Materials and Methods: A cross sectional descriptive study was conducted by selecting a convenient non-probability sample of 100 patients with chronic kidney disease (CKD) undergoing hemodialysis at Rehman Medical Institute /Dialysis center. The project duration was five months, and during this period data collection was done using the World Health Organization Quality of life (WHOQOL-BREF) questionnaire. Patients aged 18 years and above and on regular MHD for at least 3 months were included in this study. Patients with cognitive impairment and coexisting diseases such as stroke, chronic obstructive pulmonary diseases, heart diseases, and chronic liver diseases were excluded from the study as these factors could potentially affect their QOL and act as confounding factors. Results: Out of the 100 hemodialysis patients, 51% were men while 49% of the participants were females. 36% of the subjects were above 60 years old. The total score of quality of life was found to be higher in participants <60 years, of higher educational level, being very informed about the health problem, not experiencing difficulties with social or family environment, had help at home. Among them 43% subjects were not happy with their quality of life, only 13% were satisfied. Conclusion: Patients with chronic kidney disease on dialysis had overall low QOL scores in all four domains. Age, education, marital status and gender affected one or more domains of QOL in such patients. Low income status was the only independent negative predictors of QOL of patients on maintenance hemodialysis. Education level is a positive factor for improving QOL of hemodialysis patients. Keywords: quality of life, hemodialysis, WHOQOL-BREF, chronic kidney disease, End-stage renal disease (ESRD).